2020
DOI: 10.23939/ep2020.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Study of the properties of anp fertilizer encapsulated with the use of modified waste of pet

Abstract: The experimental investigation of the solubility of the prolonged-action nitroamophos obtained with the use of modified polyethylene terephthalate (PET) waste is presented. The kinetic coefficients of the diffusion process of the substances inside the shell are determined. The possibility of applying a theoretical model to predict the agro-ecological properties of encapsulated ammonium nitrate phosphate is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…We have additionally conducted small-scale studies on the effectiveness of the use of mineral fertilizers encapsulated with modified PET using crops such as potatoes, soybeans, and maize [30]. The studies have shown that the efficiency of the use of encapsulated fertilizers compared to granular fertilizers is 30-50 % higher with a lower consumption of mineral fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…We have additionally conducted small-scale studies on the effectiveness of the use of mineral fertilizers encapsulated with modified PET using crops such as potatoes, soybeans, and maize [30]. The studies have shown that the efficiency of the use of encapsulated fertilizers compared to granular fertilizers is 30-50 % higher with a lower consumption of mineral fertilizers.…”
Section: Resultsmentioning
confidence: 99%